Composition, distribution, and abundance of macrobenthos in seagrass beds of Carles, Iloilo, Philippines - Pamonag, Kaola Alezandra T.
Seagrass beds in Carles, Iloilo were sampled to determine macrobenthic composition, density and distribution as well as community indices. Sampling was done by setting a 50-meter transect in three stations within Carles and randomly collecting sediment samples form three sampling points within each transect by using a NaGISA corer. The overall mean macrobenthic density was 1,100.33 ind.?m-2 composed of organisms belonging to 52 taxa, of which 40 were polychaete species which comprised the largest density (61.7%) among the 6 major group present, namely, crustaceans (21.1%), oligochaetes (13.7%), nematodes (2.3%), nemerteans (0.6%), and turbellarians (0.6%). Among the polychaete families, Family Syllidae (29%), Nereidae (14%), Sabellidae (9%), Spionidae (9%), and Capitellidae (7%) were the most abundant. One-way ANOVA showed that densities were significantly different (F= 24.859, p=0.001) among stations. Highest macrobenthic density was in Station 3 (2,508.75 ind.?m-2) followed by Station 1 (641.33 ind.m-2) while it was lowest in Station 2 (150.90 ind. ind.?m-2). Density and diversity of macrobenthos were primarily influenced by silt and clay content (%), dissolved oxygen concentrations, turbidity, seagrass biomass and seagrass cover (R= 0.778) for seagrass provide protection form predators, stabilize sediments and increase food availability. Percent silt and clay content (R= 0.708) and median grain size (R=0.693) showed strong positive relationships with macrofaunal density, which provided optimum habitat conditions for polychaete species particularly interstitial syllids Exogone sp. and other deposit feeding macrobenthos. Species richness and diversity showed a direct linear trend with mean macrobenthic densities but species evenness was constant throughout all stations which signify equally distributed macrobenthic species populations among seagrass stations.